Evaluation of forage production and performance of Nellore heifers in different grazing methods and supplementation as a strategy to mitigate methane emissions - Lelis, Ana Laura Januário (2021)
Brazil occupies a prominent position in in livestock production, being considered one of the most important beef suppliers in the world. In order to meet the demand of a growing population, the livestock sector needs to increase its production efficiently, reducing the environmental impact, which has received numerous criticisms in animal production. In order to produce with sustainability, it is necessary to improve productivity, through adequate management of pastures and strategies that reduce the seasonal effect of forage production during certain seasons of the year. One of the strategies that can be adopted to reduce the effect of low forage availability due to seasonality is the deferred pastures associated with nutritional supplementation, which aims to improve animal efficiency and reduce the methane emission to the environmental. The objective of this study was to investigate, throughout the year, the effects of grazing methods (rotated and deferred) on the forage production potential, forage nutritional value and animal response of heifers receiving two sources of nitrogen. The study was conducted in Pirassununga - SP, Brazil. The experimental units consisted of 8 modules. Each treatment was allotted to 2 modules in a randomized block design. Twenty-four Nellore heifers (6 animals/treatment) were used. The treatments consisted of two grazing methods (deferred and rotate) and two nitrogen supplements (urea and ammonium nitrate) in a 2 x 2 factorial arrangement: 1) deferred grazing plus urea supplementation; 2) deferred grazing plus ammonium nitrate supplementation; 3) rotated grazing plus urea supplementation and 4) rotated grazing plus ammonium nitrate supplementation. The experiment lasted 1 year. The data were statistically analyzed using SAS 9.3 (SAS Institute Inc., Cary, NC, USA), considering as significant effects when P ≤ 0.05. However, these differences did not influence the final response of heifers\' performance, being similar between grazing methods. The nitrogen source did not impact CH4 production.